THE EVOLUTION OF ISLAMIC ECONOMICS: PRINCIPLES, PRACTICES, AND THE GLOBAL IMPACT OF ISLAMIC BANKING - Makhrus Ali; Rashid Rahman; Nina Anis (Journal of Noesantara Islamic Studies, 2026)
Islamic economics has emerged as an important alternative economic paradigm that integrates ethical values, legal principles, and economic activities derived from Islamic teachings. In recent decades, the rapid expansion of Islamic banking has positioned Islamic economics as a significant component of the global financial system, raising questions about its evolution, practical implementation, and broader international impact. This study aims to analyze the evolution of Islamic economics by examining its foundational principles, contemporary practices, and the global role of Islamic banking. The research employed a qualitative and descriptive-analytical approach, drawing on secondary data from academic literature, policy documents, and international financial reports related to Islamic finance. Data were analyzed through thematic and comparative analysis to explore the relationship between Islamic economic principles and institutional banking practices. The findings indicate that Islamic banking has successfully translated core Islamic economic principles, such as risk sharing, asset backing, and ethical responsibility, into modern financial operations, while also adapting pragmatically to global regulatory and market environments. The study further reveals that Islamic banking has gained global relevance by promoting ethical finance, financial inclusion, and institutional stability. The study concludes that Islamic economics represents an adaptive and evolving economic framework in which Islamic banking serves as a key mechanism for integrating ethical values into contemporary global finance.